Estágio supervisionado com uso de ambientes virtuais: possibilidades colaborativas - Luciana de Oliveira Silva (2013)
Educational practices must be reinvented in times of technology and the teacher preparation course is the starting point for rethinking these practices. During the school traineeship, crucial moment for theory and practice articulation, teachers experiences must be communicated and interconnected, with active intervention from the supervisor and with constant dialogue about the usage of technology and information resources. The digital students these future teachers will meet and the necessity of a virtual reflection and collaboration net along the teacher preparation course justify this study, which investigates the virtual learning environment as a collaborative possibility for the supervised teachers traineeship and as a valuable space for the development of the digital competence. Considering the virtual environment a huge system in which elements act and interact and behavior patterns emerge from the relationship of the participants and the context, I adopt the Complexity theory and the Situated Learning theory to guide my investigation. These two approaches consider the reciprocal and interdependent character of learners, activity and context, which makes possible the emergence of differentiated practices resulting from negotiations. The study has a qualitative nature, adopting the virtual ethnography principles (HINE, 2000). The environment is the source of data and the focus is on the emergent processes of the research. The researcher is the human instrument of data collecting, which affects the system and is affected by the investigated culture. Data was collected from online interactions among pre-service teachers in a course at FALE/UFMG, from the researchers notes during the traineeship that happened in a middle school and from a questionnaire the pre-service teachers answered at the end of the course. They show that the virtual learning environment has the necessary basis for knowledge construction, creating good space for interaction, virtual immersion, collective construction and reflection, which are important aspects in teachers preparation. The community atmosphere the virtual learning environment suggests favors the development of the digital competence and the acquisition of the necessary basis for a successful pedagogical action.